ANALISIS MAQÂṢID ASY-SYARÎ’AH TERHADAP PUTUSAN MK NOMOR 46/PUU-VIII/2010 DAN IMPLIKASINYA TERHADAP HUKUM KELUARGA ISLAM DI INDONESIA - Rikza, Muhammad Ubayyu; Djazimah, Siti (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2017)
The Constitutional Court made a revolutionary decision through the decision of Constitutional Court Number 46/PUU-VIII/2010 about the status of children outside of marriage. The decision stated that childrens born outside of marriage not only had a civil relationship with their mother and mother's family but also had a civil relationship with their biological father. Its implicates that children outside of marriage have the same rights with legal children, such as earning a living, inheritance and equality before the law. Seen from the concept of maqâṣid asy-syarî'ah, the decision does not violate the Islamic law, otherwhise it is in the line with the principles of maqâṣid asy-syarî'ah especially the principles of ḥifẓ an-nasl and ḥifẓ an-nafs. [Mahkamah Konstitusi telah membuat putusan revolusioner dalam putusan MK Nomor 46/PUU-VIII/2010 tentang status anak di luar perkawinan. Putusan tersebut menyatakan bahwa anak yang dilahirkan di luar perkawinan mempunyai hubungan perdata dengan ibu dan keluarga ibunya dan mempunyai hubungan perdata dengan ayah biologisnya yang dibuktikan berdasarkan ilmu pengetahuan dan teknologi. Implikasinya adalah anak di luar perkawinan mendapat hak sama dengan anak sah, mendapatkan nafkah, waris dan persamaan di hadapan hukum. Dilihat dari konsep maqâṣid asy-syarî’ah, putusan tersebut tidak melanggar hukum Islam, sebaliknya, ia sejalan dengan prinsip-prinsip maqâṣid asy-syarî’ah terutama prinsip ḥifẓ an-nasl dan ḥifẓ an-nafs.]